Endothelin receptor antagonists: effects on extracellular matrix synthesis in primary cultures of skin fibroblasts from systemic sclerosis patients - B. Villaggio; B. Seriolo; A. Sulli; A. Parodio; C. Ferrone; R. Brizzolara; P. Montagna; S. Soldano; M. Cutolo (PAGEPress Publications, 2012)
Endothelin-1 (ET-1) seems to enhance the pro-fibrotic protein synthesis by skin fibroblasts and its effects are mediated by endothelin-A and B (ETA and ETB) receptors. This study aimed to investigate the effects of ETA and ETB receptor antagonists (ETARA-sitaxentan and ETA/BRA-bosentan) on type I collagen (COL-1), fibronectin (FN) and fibrillin-1 (FBL-1) synthesis in primary cultures of skin fibroblasts from systemic sclerosis patients. Primary cultures of fibroblasts were obtained from skin biopsies of 6 female systemic sclerosis patients and were treated with ET-1 (100 nM) for 24 and 48 hrs with or without pre-treatment (1 hr) with ETARA (2 μM) or ETA/BRA (10 μM). Primary culture of human scleroderma skin fibroblasts not treated with ET-1 or ET receptor antagonists (ETARA and ETA/BRA) were used as controls. COL-1, FN and FBL-1 synthesis was evaluated by immunocytochemistry and Western blot analysis. Immunocytochemistry and Western blot analysis showed that ET-1 significantly increased COL-1 and FN synthesis at 24 and 48 hrs and FBL-1 synthesis at 48 hrs vs untreated cells. ETARA significantly contrasted the ET-1-mediated increase in COL-1 and FN at 24 hrs as well as COL-1 and FBL-1 at 48 hrs, but not FN synthesis vs ET-1-treated fibroblasts. Conversely, ETA/BRA significantly antagonized the ET-1-mediated overproduction of COL-1 and FN both at 24 and 48 hrs and the FBL-1 synthesis at 48 hrs vs ET-1-treated cells. The single ETARA treatment seems to contrast significantly the increase in COL-1 synthesis, whereas the dual ETA/BRA treatment seems active in significantly antagonizing both COL-1 and FN overproduction induced by ET-1. In conclusion, ET-1 antagonism might have positive effects in contrasting the profibrotic activity of systemic sclerosis skin fibroblasts.